When a Desquamating Rash Leads to a Challenging Diagnosis - Differential diagnosis of a desquamating rash - Almeida, Sara Isabel De (2021)
A desquamating rash may pose a true clinical challenge. Therefore, history and clinical course are crucial to do an accurate diagnosis. We present a case of a 17 year-old boy submitted to a pilonidalis sinus excision, who presented to the emergency department with erythema and desquamation of lips, a scarlatiniform rash, an extensive desquamation of hands and feet and infection of the surgical site.  Given the suspicion of a staphylococcal scalded skin syndrome intravenous antibiotics were immediately started. During day sixth of admission a sudden itching erythematous and desquamative rash appeared on the face and body, which was worse after administration of cefuroxime. This antibiotic was stopped and it was noticed a clinical improvement. Skin biopsy revealed toxiderma. At follow-up a positive oral provocation test for cefuroxime confirmed the cause of toxiderma. This case brings out to discussion the importance of clinical course to make the correct diagnosis.